1987
DOI: 10.1055/s-2007-1011902
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metabolic and Hormonal Effects of Calcitonin and Somatostatin (SRIF) in the Course of Oral Glucose Tolerance Test (OGTT)

Abstract: A comparison is presented of the effect of two therapeutic doses of synthetic somatostatin (250 and 500 micrograms) and salmon calcitonin (50 and 100 U) on the blood levels of sugar, insulin (IRI), somatotropin (HGH) and cortisol in healthy volunteers following peroral administration of 75 g of glucose. Calcitonin was responsible for a significant change in glycaemia as well as IRI levels: following a retarded enhancement glycaemia as well as insulinaemia through out the first 15-30 minutes of OGTT, increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Eel and human calcitonin are reported not to affect basal prolactin release (Kaji et al, 1985;Looij etal., 1988). The prolactin increment in response to TRH has uniformly been reported to be inhibited by salmon calcitonin (Isaac et al, 1980;Ceda et al, 1982;Zofkova & Nedvidkova, 1984) although porcine and eel calcitonin are said not to have any effect (Barreca et al, 1980;Kaji er al., 1985). Likewise theTSH response to TRH is inhibited by salmon calcitonin (Isaac et al, 1980;Ceda et al, 1982;Zofkova & Bednar, 1984;Leicht et al 1974) although this was not found with the porcine variety (Barreca et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Eel and human calcitonin are reported not to affect basal prolactin release (Kaji et al, 1985;Looij etal., 1988). The prolactin increment in response to TRH has uniformly been reported to be inhibited by salmon calcitonin (Isaac et al, 1980;Ceda et al, 1982;Zofkova & Nedvidkova, 1984) although porcine and eel calcitonin are said not to have any effect (Barreca et al, 1980;Kaji er al., 1985). Likewise theTSH response to TRH is inhibited by salmon calcitonin (Isaac et al, 1980;Ceda et al, 1982;Zofkova & Bednar, 1984;Leicht et al 1974) although this was not found with the porcine variety (Barreca et al, 1980).…”
Section: Discussionmentioning
confidence: 99%